Role of interferon-alpha 2b and octreotide in prevention of experimentally induced corneal neovascularization in rats - Demir, Tamer; Ulaş, Fatih; Özkaya Çeliker, Ülkü (My University, 2003)
Purpose: To investigate the effects of interferon-alpha2b (IFN-?2b) and octreotide, a long-acting analogue of somatostatin, on experimentally induced corneal neovascularization. Methods: Chemical keratitis was induced unilaterally in the eyes of 30 rats by silver nitrate cauterization. Ten of these animals received subcutaneous IFN-?2b (250,000 IU) four times every other day (interferon group) and ten rats were infected with octreotide (10 ?g) (octreotide group). The remaining ten rats were used as controls. The corneas of all animals were biomicroscopically and histopathologically examined on day 8 by electron microscope to observe whether there was inhibition of neovascularization or not. Results: Corneal neovascularization and histopathological scores were lower in both the interferon group (p<0.005) and the octreotide group (p<0.001) compared to the controls. These parameters were lower in the octreotide group compared with the interferon-injected rats (p<0.05). Conclusion: We suggest that the application of both IFN-a2b and octreotide is effective in the inhibition of corneal neovascularization and these preventive effects were more significant in the latter group.
Keywords: Alpha Interferon; Corneal Neovascularization; Octreotide